2019
DOI: 10.3390/su11205722
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Housing Vacancy Rates in Rural China Using Power Consumption Data

Abstract: Village hollowing is a growing policy problem globally, but accurately estimating housing vacancy rates is difficult and costly. In this study, we piloted the use of power consumption data to estimate the vacancy rate of rural housing. To illustrate the method used, we took power consumption data in 2014 and 2017 in an area of rural China to analyze the change in housing vacancies. Results indicated that the rural vacancy rates were 5.27% and 8.69%, respectively, while underutilization rates were around 10% in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Based on the results of the life satisfaction questionnaire after land consolidation, we found that improvement in housing quality and better neighborhood environment and facilities increase the life satisfaction of villagers. China is still at an early stage of accelerated urbanization and how the government decides to utilize rural land and labor resources, and how they can find a more balanced approach to development that reduces the disparities between rural and urban inhabitants both have serious implications in sustaining the economic prosperity of the country [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of the life satisfaction questionnaire after land consolidation, we found that improvement in housing quality and better neighborhood environment and facilities increase the life satisfaction of villagers. China is still at an early stage of accelerated urbanization and how the government decides to utilize rural land and labor resources, and how they can find a more balanced approach to development that reduces the disparities between rural and urban inhabitants both have serious implications in sustaining the economic prosperity of the country [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…After the reform in 1978, the relaxation of mobility control and new economic opportunities in coastal regions resulted in a massive flow of rural surplus labor to the cities, estimated to be around 290 million people [1,2]. This massive flow of migration is an important driver of urbanization and industrialization but also creates problems of rural depopulation and decline, especially in the poorer inland regions [3][4][5][6]. Second, a trend of return-migration has been emerging, with rural migrants moving back to the countryside and small towns.…”
Section: Introductionmentioning
confidence: 99%
“…Third, urban studies tend to focus on the impact of rural-to-urban migration on urban development and its challenges, such as housing, social exclusion, and integration [36][37][38][39]. Fourth, a number of studies exist from the perspective of rural studies, with a strong focus on examining the impact of the outflow of rural residents, such as rural hollowing, rural poverty, and social issues such as inequality, neglected children and elderly people [4,[40][41][42][43]. Of particular relevance to this study, research on the factors influencing population migration in China can be classified into two major groups.…”
Section: Introductionmentioning
confidence: 99%
“…At the macro scale, some studies have observed a non-coupling relationship between the rural population decline and increased rural housing areas [14,15]. In addition, empirical studies have put forward many methodologies in describing the phenomenon of RHV [16,17].…”
Section: Introductionmentioning
confidence: 99%